Clinical significance of visceral pleural and lymphovascular invasion in surgically resected adenosquamous lung cancer. (17th November 2020) - Wang, Yanan; Qian, Fangfei; Hu, Minjuan; Chen, Ya; Yang, Zhengyu; Han, Baohui
Abstract: OBJECTIVES: The aim of this study was to assess the relationship between visceral pleural invasion (VPI), lymphovascular invasion (LVI) and other clinicopathological characteristics and their prognostic impact on surgically resected adenosquamous carcinoma (ASC). METHODS: We retrospectively reviewed 256 patients with radically resected ASC between January 2010 and December 2015. Patients were divided into 2 groups: those with VPI and those with LVI. The effects of VPI and LVI on disease-free survival and overall survival were evaluated, further stratified by tumour size and lymph node status. RESULTS: Finally, 213 patients with ASC were enrolled in our study. VPI was correlated with tumour location ( P  < 0.001), pT stage ( P  < 0.001) and pN stage ( P  = 0.012). LVI was related to age ( P  = 0.005) and pN stage ( P  = 0.003). Both VPI and LVI were adverse prognostic factors for disease-free survival ( P  = 0.008, P  = 0.028) and overall survival ( P  = 0.005, P  = 0.009) using the Kaplan–Meier method. In multivariable analysis only, VPI was an independent risk factor for disease-free survival [hazard ratio (HR) 0.61, 95% confidence interval (CI) 0.42–0.87; false discovery rate, adjusted P  = 0.020] and overall survival (HR 0.60, 95% CI 0.42–0.86; false discovery rate, adjusted P  = 0.017). When the prognostic value of VPI was stratified by tumour size and lymph node status, we observed that only patients with VPI in tumours ≤4 cm and patients with N0 status had a worse prognosis than those without visceral invasion ( P  < 0.05). CONCLUSIONS: VPI and LVI were poor prognostic factors in patients with ASC, but only VPI was an independent factor for survival, especially in patients with tumours ≤4 cm and pN0 status.